Implementation of Discovery Learning Method to Improve Student Learning Outcomes in Science Learning at MI Tarbiyatul Islamiyah Winong - Nikmah, Uswatun; Andriani, Vifi; Zuliastuti, Vivi; Ruhansah, Vina Inayati; Chasanah, Uswatun (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes on animal life cycle materials through the application of the Discovery Learning method. This research was conducted at MI Tarbiyatul Islamiyah Winong with 3rd grade students with 30 students. The research method used is class action research (PTK) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The results of the study show that the application of the Discovery Learning method can increase student involvement in learning, motivate students to actively seek information, and develop their critical thinking skills. In cycle I, the average student learning outcome was 70%, and after the application of this method in cycle II, the average student learning outcome increased to 85%. This improvement shows that the Discovery Learning method is effective in improving student learning outcomes, especially in animal life cycle materials. Thus, it can be concluded that the application of the Discovery Learning method can improve the understanding and learning outcomes of 3rd grade students of MI Tarbiyatul Islamiyah Winong.